2015
DOI: 10.2140/gt.2015.19.1155
|View full text |Cite
|
Sign up to set email alerts
|

The homotopy type of spaces of locally convex curves in the sphere

Abstract: A smooth curve γ : [0, 1] → S 2 is locally convex if its geodesic curvature is positive at every point. J. A. Little showed that the space of all locally convex curves γ with γ(0) = γ(1) = e 1 and γThe space L −1,c is known to be contractible. We prove that L +1 and L −1,n are homotopy equivalent to (ΩS 3 ) ∨ S 2 ∨ S 6 ∨ S 10 ∨ · · · and (ΩS 3 ) ∨ S 4 ∨ S 8 ∨ S 12 ∨ · · · , respectively. As a corollary, we deduce the homotopy type of the components of the space Free(S 1 , S 2 ) of free curves γ : S 1 → S 2 (i.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(53 citation statements)
references
References 27 publications
1
52
0
Order By: Relevance
“…In this book it is shown that the loop space ΩS Observe that L ρ 0 (Q) ⊂ I(Q). It is known from an analogous result of [22] that the inclusion map i : L ρ 0 (Q) → I(Q) induces a surjetive map on homology (refer Proposition 3.20):…”
Section: ωSmentioning
confidence: 99%
See 4 more Smart Citations
“…In this book it is shown that the loop space ΩS Observe that L ρ 0 (Q) ⊂ I(Q). It is known from an analogous result of [22] that the inclusion map i : L ρ 0 (Q) → I(Q) induces a surjetive map on homology (refer Proposition 3.20):…”
Section: ωSmentioning
confidence: 99%
“…A. Khesin [31] studied the topology of the space of all smooth immersed curves (not necessarily closed) with positive geodesic curvature on S 2 which start and end at given points and given directions and found the number of connected components of this space. [20], [21] and [22], N. C. Saldanha did several further works compared to Theorems 1.1 and 1.2 on the higher homotopy properties of the space of curves with positive geodesic curvature in S 2 . More precisely, he proved the following result: …”
Section: Topology Of the Space Of Curves In 2-spherementioning
confidence: 99%
See 3 more Smart Citations